An investigation of the inflammatory cytokine and chemokine network in systemic sclerosis. Issue 6 (1st February 2011) - Codullo, Veronica; Baldwin, Helen M; Singh, Mark D; Fraser, Alasdair R; Wilson, Catherine; Gilmour, Ashley; Hueber, Axel J; Bonino, Claudia; McInnes, Iain B; Montecucco, Carlomaurizio; Graham, Gerard J
Abstract : Objectives: Systemic sclerosis (SSc) is characterised by vasculopathy, an aberrantly activated immune system and excessive extracellular matrix deposition. Inflammatory chemokines control migration of cells to sites of tissue damage; their removal from inflamed sites is essential for resolution of the inflammatory response. The atypical chemokine receptor D6 has a critical role in this physiological balance. To explore potential deregulation of this system in SSc, inflammatory chemokine and D6 expression were compared with that in healthy controls (HC). Methods: Serum levels of inflammatory mediators were assessed by luminex analysis. Peripheral blood mononuclear cells (PBMCs) were used in molecular and immunocytochemical analysis. Platelet-rich plasma was collected and assessed by western blotting for D6 expression levels. Sex-matched HC were used for comparison. Results: 72 patients with SSc and 30 HC were enrolled in the study. The chemokines MCP-1/CCL2, MIP-1α/CCL3, MIP-1β/CCL4 and IL-8/CXCL8 were significantly increased in patients with SSc, regardless of disease subtype and phase. Quantitative PCR analysis revealed a significant 10-fold upregulation of D6 transcripts in patients with SSc compared with controls, and this was paralleled by increased D6 protein expression in the PBMCs of patients with SSc. Platelet lysates also showed strong D6 expression in patients with SSc but not in controls. Importantly, high levels of D6 expression correlated with reduced levels of its ligands in serum. Conclusions: Inflammatory chemokines and the regulatory receptor D6 are significantly upregulated in SSc and high D6 levels are associated with lower systemic chemokine levels, indicating that some patients control systemic chemokine levels using D6. These results suggest that chemokines may represent a therapeutic target in SSc.